ANALISIS METODE HYPNOTEACHING PADA PEMBELAJARAN MATEMATIKA SISWA SD - Dewi Nursiami; Oman Suryaman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the use of hypnoteaching learning methods in mathematics learning for students at SD Negeri 1 Sidamulya. The question to be answered in this research is: How do elementary school students learn mathematics using the hypnoteaching method. To answer this question, this research uses a qualitative research approach with descriptive methods. In accordance with the form of a qualitative approach and the data sources that will be used, the data collection techniques used are observation analysis, interviews and documentation. Meanwhile, in analyzing the data, researchers used qualitative descriptive analysis techniques. Based on research conducted by researchers, the hypnoteaching method is used by the fourth grade homeroom teacher when teaching mathematics. From the results of the analysis of this research, it can be concluded that the use of the hypnoteaching method in mathematics learning for fourth grade elementary school students at SD Negeri 1 Sidamulya, is very helpful for teachers in establishing good interactions between teachers and students. Apart from that, learning mathematics is often considered difficult after teachers use the hypnoteaching method, there are changes in students' assumptions about learning mathematics. Apart from that, students also think that teachers who teach mathematics seem boring, students are often reluctant to ask questions to the teacher because the interaction or relationship between the teacher and students is less than harmonious. The student's personality level also looks much better. The students are very enthusiastic and passionate about studying mathematics. The positive affirmations and motivation that the teacher always gives to students are able to convince students to study harder, have a much greater curiosity and level of student self-confidence. much braver to carry out various positive activities during class learning.